A Review on Additive Manufacturing Technology - Mhetre, Gurudev N; Jadhav, Vijay S; Deshmukh, Suhas P; Thakar, Chetan M (ECS transactions, 2022)
Additive manufacturing is a new, rapidly emerging technique in the industrial sector. This is the process of creating parts by adding layer by layer material, hence it is called as 'Layer Manufacturing Process.’ This process is also called ‘Rapid Prototyping’ or ‘3DPrinting.’ This is a tool-less manufacturing method that produces parts in less time and with high precision. This process provides freedom for designing the parts and their complexity. Additive manufacturing has many advantages over conventional manufacturing processes like low production cost, no residual stresses, no wastage of material, etc. Nowadays, so much research work is going on in this additive manufacturing field. This manufacturing technology is going to replace the conventional manufacturing techniques in the upcoming days. In this paper, we discuss about the various additive manufacturing methods, its principles, applications, advantages, and challenges to industrial use.